Gas relative permeability evaluation in tight rocks using rate-transient analysis (RTA) techniques. (June 2023) - Shabani, Mohammadebrahim; Ghanizadeh, Amin; Clarkson, Christopher R.
Abstract: The evaluation of effective and relative gas permeability is critical for modeling hydrocarbon recovery from low-permeability (unconventional) reservoirs, and for evaluating the potential for clean energy pathways such as carbon capture and sequestration and hydrogen storage in subsurface. Nevertheless, due to the low flow rates and long experimental times associated with low-permeability (nanodarcy/microdarcy range) sample testing, measuring relative permeability through conventional techniques is technically challenging, time-consuming, and expensive. Additionally, and importantly, none of the routine laboratory techniques for measuring relative permeability can mimic the boundary conditions under which wells are produced from, or injected into, in the field. For the first time, effective and relative gas permeability of partially-saturated low-permeability sedimentary rocks were investigated using state-of-the-art core analysis techniques based on rate-transient analysis (RTA). Conventional and new straight-line analysis methods, commonly applied to production data in the field, were used to estimate effective gas permeability of core plugs under variable stress conditions and water saturations. Five low-permeability siltstone and organic/clay-rich samples, differing in mineralogy, porosity, and pore size distribution, were analyzed for proof-of-concept testing. The observed flow regimes consist of transient linear flow followed by boundary-dominated flow regimes, as previously reported for field data. Satisfactory correlation (average coefficient of variation less than 7%) between permeability estimates using different RTA techniques demonstrates the applicability of this method for effective and relative permeability assessment of partially-saturated ultra-tight reservoirs (down to less than 1.0∙10 −5 md). Importantly, test times after the initiation of the production phase, were on the order of minutes, which is significantly shorter than those commonly achievable using conventional techniques (e.g., hours using pulse-decay gas permeability testing). Effective gas permeability (from 1.5∙10 −3 to 7.5∙10 −6 md), and slip factor (from 715 to −286 psia −1 ), decreased with increasing water saturation (0–53%), reflecting the lower contribution of slip flow to gas transport. Effective gas permeability decreased with increasing effective stress (500–4000 psia), likely due to reduced effective (transport) pore throat size and increased tortuosity. The reduction of slip factor and the observed stress dependency with water saturation is attributed to the channel flow mechanism. Highlights: Effective gas permeability of core plugs was estimated using RTAPK methods under varying stress and water saturation. Five low-permeability samples with different mineralogy and porosity were tested using RTAPK for proof-of-concept. RTAPK method was demostated to be effective for assessing permeability in partially-saturated ultra-tight reservoirs. RTAPK testing takes minutes, significantly shorter than conventional methods for effective permeability measuement.